First, rewrite the equation as:
3.8x^2 - color(red)(4.7x) + color(blue)(2.1) = 4.7x - color(red)(4.7x) - 2.1 + color(blue)(2.1)
3.8x^2 - 4.7x + 2.1 = 0 - 0
3.8x^2 - 4.7x + 2.1 = 0
Now, we can use the quadratic equation to solve this problem:
The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0, the values of x which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))
Substituting:
color(red)(3.8) for color(red)(a)
color(blue)(-4.7) for color(blue)(b)
color(green)(2.1) for color(green)(c) gives:
x = (-color(blue)((-4.7)) +- sqrt(color(blue)((-4.7))^2 - (4 * color(red)(3.8) * color(green)(2.1))))/(2 * color(red)(3.8))
x = (4.7 +- sqrt(22.09 - 31.92))/7.6
x = (4.7 +- sqrt(-9.83))/7.6